Dielectric loaded TEM horn-fed ridged horn antenna design for ultrawideband ground-penetrating impulse radar - Turk, Ahmet Serdar; Keskin, Ahmet Kenan; Senturk, Mustafa Dagcan (Tubitak Scientific & Technological Research Council Turkey, 2015)
A modified double-ridged horn structure is proposed to obtain ultrawideband antenna characteristics over a bandwidth ratio of greater than 40:1 for impulse radar systems. The Vivaldi-shaped TEM horn feeder has been designed to extend the lower cut-off frequency and the partial dielectric loading technique using a small lens inward while the aperture has been implemented to enhance the gain of the standard double-ridged horn antenna without changing the physical dimensions. The starting frequency of the antenna operation band is lowered from 800 MHz to 400 MHz. Moreover, approximately 5 dB gain increment level is achieved from 4 to 10 GHz. It is shown that proper combination of the partial dielectric loaded TEM and ridged horn antennas can be suitable for multiband ground-penetrating radar operations that provide high resolution imaging at different depths. The antenna gain and input reflection performance measurements are presented with comparisons in both the frequency and time domains.
Keywords: Ultrawideband antennas; dielectric loaded TEM horn; double-ridged horn; ground-penetrating radar; impulse radiator; Computer Science; Engineering